Robert’s uterus: a rare mullerian anomaly mystery unfolded - Devi, T. Ramani; Devi, C. Archana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Anomalies of female genital tract may not be detected until after menarche when they present a cyclical pain due to outlet obstruction. Mullerian anomalies represent a vast array of structural abnormalities resulting from improper development and fusion of embryological mullerian ducts. 19-year-old girl attained menarche at the age of 14, had progressive dysmenorrhoea and diagnosed as right haemotosalphinx and ovarian endometrioma which were removed in 2008. As pain progressed, she underwent laparoscopic adhesiolysis in 2013. Since, pain persisted, diagnosed as right haematometra, and drainage done by laparotomy. Left adnexa were normal. She was given depot provera till she completed schooling. She developed recurrent dysmenorrhoea after stopping depot provera. USG and MRI revealed recurrent haematometra on right side with normal left horn. The possibility of atypical septum was thought about and hystero laparoscopy was done. It showed right side haemetometra with absent right adnexa. Left adnexa normal. Hysteroscopy showed normal left horn with septum with a bulge towards the left side. Hence, proceeded with hysteroscopic septostomy and haemetometra was drained to the left horn. Later patient was free from dysmenorrhea and repeat hysteroscopy was found to be normal. This case highlighting mullerian anomalies have to be considered when young girls present with severe progressive dysmenorrhoea and diagnosis remains a challenge most of the clinicians. This rare entity has to be kept in mind while evaluating such patients. Prompt diagnosis and early surgical correction are essential to avoid future morbidity in the form of repeated unnecessary surgeries.